REMOTE AUDIT UNTUK MENINGKATKAN EFEKTIVITAS DAN EFISIENSI - novia Mega Putri; Salsabila Aprilia; Tri Ratnawati (Jurnal Ilmu Akuntansi, 2024)
This research aims to examine the effectiveness and efficiency of remote audits in the context of modern auditing, identify the challenges faced, and provide solutions to overcome these challenges. Remote audits use information and communication technology to carry out the audit process remotely, offering flexibility and significant cost savings. However, its implementation faces various challenges such as data security and technology gaps. This research uses qualitative descriptive approach data through literature studies to analyze the benefits, challenges and solutions in implementing remote audits. The research results show that remote audits can increase audit effectiveness and efficiency through real-time access to data and flexibility in audit implementation. However, to optimize these benefits, strong data security measures and adequate technology training are needed for auditors and audited entities.